DESIGN AND EVALUATION OF PROPOLIS-HPC/PVP ELECTROSPUN NANOFIBERS FOR POSSIBLE CUTANEOUS APPLICATIONS - Esenturk-Guzel, Imren; Yapar, Evren Algin; Cavalu, Simona; Seker, Brahim Tugkan; Inal, Ebrar; Kartal, Murat; Koc, Rabia Cakir; Ozturk, Rabia Yilmaz; Goksu, Feriha; Bolek, Sibel; Turkmen, Ayyuce (SOC STIINTE FARMACEUTICE ROMANIA, 2024)
The aim of the study was to prepare propolis loaded hydroxypropyl cellulose and polyvinyl pyrrolidone (HPC/PVP) nanofibers, suitable for cutaneous applications. LC-HRMS analyses were applied for the identification and quantification of the bio-compounds in the propolis extract. Electrospinning was applied in order to prepare propolis HPC/PVP nanofibers with increasing concentration of propolis 10%, 20% and 30 % (v/v) and subsequently characterized in terms of morphology, wettability, thermal degradation and biological properties. SEM images showed homogenous features of the nanofibers and average diameter between 197.2 - 268.4 nm, high antioxidant activity, very good biocompatibility and no cytotoxicity. Particularly, with the highest propolis concentration, 30-PE/HPC/PVP nanofiber formulation is a promising alternative to conventional treatments for cutaneous applications.
Keywords: electrospinning; nanofibers; propolis; polyvinyl pyrollidone; hdroxypropylcellulose; biocompatibility; ANTIBACTERIAL; Pharmacology & Pharmacy